POLITICAL DISCOURSE DURING CRISIS: DISCURSIVE STRATEGIES IN PRESIDENTIAL COVID-19 SPEECHES - Osei Yaw Akoto; Sanka Washew; Kwasi Sarfo-Adu (Universitas Islam Sumatera Utara (UISU), 2026)
This study investigates the discursive strategies employed by Ghana’s President, Nana Akufo-Addo, in his public addresses on the COVID-19 pandemic. The corpus consists of twenty-nine televised national update speeches delivered between March 2020 and May 2023. Socio-cognitive model of critical discourse analysis, the study examines how discursive strategies are used to construct ideological representations, shape public consciousness, and sustain political legitimacy during a period of national crisis. Employing a qualitative interpretive approach, the analysis identifies eighteen discursive strategies, including authority, metaphor, number game, evidentiality, victimization, comparison, and national self-glorification. These strategies are strategically deployed to construct ideological polarization, mobilize public emotions, justify governmental interventions, and reinforce presidential authority and national unity. The findings reveal how political discourse functions not merely as communication, but also as a mechanism of persuasion, ideological reproduction, and crisis management. The study contributes to scholarship on political discourse, critical discourse analysis, and crisis communication by demonstrating how rhetorical and ideological resources shape public perception and legitimize political power during national emergencies.